Perceptions and Experiences of Health Care Workers on Accountability Mechanisms for Enhancing Quality Improvement in the Delivery of Maternal Newborns and Child Health Services in Mkuranga, Tanzania - August, Francis; Nyamhanga, Tumaini; Kakoko, Deodatus; Nathanaeli, Sirili; Frumence, Gasto (Frontiers in Global Women's Health, 2022)
Globally, 302,000 maternal deaths occur annually; more strikingly, 99% of them happen in low and middle-income countries, including Tanzania. There has been insufficient progress in improving maternal and newborn health despite an investment of resources to enhance the quality of maternal health in terms of training and deploying human resources for health, constructing health facilities, and supplying medical products. However, fewer efforts are invested in enhancing accountability towards the improvement of the quality of maternal health care. We explore the perceptions of healthcare workers regarding accountability mechanisms for enhancing quality improvement in the delivery of maternal health care services.. We adopted a qualitative study design, whereas phenomenology was used as a study design to understand how health workers perceive accountability, and data were collected using semi-structured interviews. We then used thematic analysis to analyze themes and sub-themes. Results: Findings showed differences in the conceptualization of accountability and accountability mechanisms among the participants; where some view it as adherence to ethics and procedures. We highlighted several tools for enhancing quality improvement in the delivery of maternal health services. This includes clinical meetings, attendance tracking, maternal audits, and ward rounds. The accountability mechanisms seem to trigger or enforce accountability positively where other health system factors remain constant, while in other contexts where other supply factors are inadequate, the tools were somewhat deterrent. Health care workers perceived accountability mechanisms as useful for inculcating the spirit of hard work in the delivery of maternal health services. However, without solving health system bottlenecks like the inadequate supply of medical equipment and insufficient human resource for health, it will be difficult to enforce accountability mechanisms for improvement in maternal care Perceived variations in the understanding of accountability among healthcare workers signaled a proper but fragmented understanding of accountability in maternal care. Accountability mechanisms are perceived to be useful for enhancing hard work in the provision of maternal health services. Moreover, inadequate motivation resulting from health system bottlenecks tend to constrain enforcement of accountability in the provision of maternal care services. We recommend the government should deal with health system constraints and enforce regular monitoring and supervision